Molecular characterization of peste des petits ruminants virus strains circulating in sheep and goats in Iran - Babaoglu, AR; Mahzounieh, M; Bilge Dagalp, S (Journal of the Hellenic Veterinary Medical Society, 2024)
Peste des petits ruminants virus (PPRV) infection is an acute to sub-acute viral disease in both domestic and wild small ruminants. Recent outbreaks of PPRV in Turkey’s Marmara region and in Europe (Georgia and Bulgaria) highlight the potential risk of PPR spreading to a larger geographic area. In order to achieve a successful control and eradication program, evaluating etiyological data prior to developing disease control strategies is an essential criterion. The aim of this study was to perform molecular characterization of PPRVs found in sheep and goats in Iran. For this purpose, a total of 341 animal specimens were collected from sheep (n = 271) and goats (n = 70) with clinical signs of PPRV infection from twelve different provinces. RT-real time-qPCR assay based on nucleoprotein (N) with a plasmid standard reference, which is rapid and sensitive for the diagnosis of infection, was used for the detection of PPRV nucleic acid. In the RT-real time-qPCR assay, a positivity rate of 29,91% (102/341) was detected for PPRV nucleic acid. At the nucleotide level, the N-gene partial sequence analysis of sixteen viral sequences obtained from four provinces of Iran showed 96.8%-100% similarity and 97.6%-100% and 88.2%-89% similarity to the Turkey2000 reference isolate and Nigeria 75/1 vaccine strain, respectively. Except for two viral sequences, the secondary protein structure of the approximately 80 amino acid long nucleoprotein region in the sixteen viral sequences revealed structural similarity in the alpha-helix and beta-leaf structures for all PPRVs of Iranian origin. In the phylogenetic tree, PPRVs circulating in Iran are homologous, belong to genetic lineage IV, and are closely related to the Turkey2000 isolate. According to the results of this work, it is emphasized that PPRV circulates in Iran, causes outbreaks and deaths, and should be controlled. In addition, further studies on the molecular analyses of the N protein of the Iranian isolates will help clarify the origin of the disease and determine the genetic diversity of the virus.